Pengelolaan Komponen Biotik dan Abiotik di Kawasan Kompleks Gedung Parlemen DPR RI Jakarta - Hugua Hugua; Alia Rahmatillah; Dinnur Garista Wirawan (Rekayasa, 2022)
This research was conducted at the DPR RI Building Office in September 2022 with the aim of examining the extent to which management influences the Biotic, Abiotic and Cultural Environment in realizing the DPR RI as a Modern Parliament with a sample of 30 people from DPR RI Office Employees. This study uses a descriptive quantitative method, namely research that describes the research object at the current state based on the facts as they are, then analyzed and interpreted using IBM SPSS Version 27 Software. The research results of the biotic environment variable (X1) have a positive and significant effect on the manifestation of the DPR RI as a modern parliament complex (Y) with an R value of 0.877, while the coefficient of determination (R2) is 0.769 or 76.9%. This shows that the biotic environment variable (X1) has a contribution of 76.9% to the realization of the DPR RI as a modern parliament (Y) variable. The abiotic environment variable (X2) has a positive and significant effect on the Realization of the DPR RI as a modern parliament (Y), the R value is 0.786. While the coefficient of determination (R2) is 0.617 or 61.7%. This shows that the Abiotic Environment variable (X2) has a contribution of 61.7% to the Realization of the DPR RI as a Modern Parliament (Y) variable. Biotic environment (X1), abiotic environment (X2) and cultural (X3) variables have a positive and significant effect on the realization of the DPR RI as a modern parliament (Y). The R value is 0.945, while the coefficient of determination (R2) is 0.893 or 89.3%.